33rd Annual Meeting & Pre-Conference Programs of the Society for Immunotherapy of Cancer (SITC 2018) (Drug and therapeutics bulletin, 2024)
Poster PresentationsCo-Stimulatory Ligand-Receptor InteractionP397 Ectopic Tim-3 expression on T regulatory cells leads to lymphoproliferation and T cell activationHridesh Banerjee, Héctor Nieves-Rosado, Lawrence P. Kane, Ph.D.University of Pittsburgh, Pittsburgh, PA, USACorrespondence: Lawrence P. Kane (lkane@pitt.edu) Background T cell (or transmembrane) immunoglobulin and mucin domain 3 (Tim-3) is a transmembrane protein that has been associated with both inhibitory and co-stimulatory function in T cells. In tumor-infiltrating (TI) T cells and during chronic infection, Tim-3 has been seen to be expressed in terminally exhausted T cells and a significant proportion of regulatory T cells (Treg). However, what role Tim-3 plays in Treg is still unclear. Another factor complicating the role of Tim-3 is that along with Tim-3, other checkpoint receptors such as PD-1 are also upregulated in TI-Treg and very little is known about crosstalk between various checkpoint receptors in effector T cells and Treg. Methods To investigate the role of Tim-3 in Treg, we used two mouse models, a constitutive Tim-3/Treg model (Foxp3-YFP-Cre x flox-stop-flox Tim-3) and a tamoxifen-inducible Treg/Tim-3 model (Foxp3-CreERT2 x flox-stop-flox Tim- 3).Basic characterisation of the immune system specifically the lyymphoid compartment and T cells including Treg cells was carried out. Functional assays on T regulatory cells was also done to look at effect of TIM-3 expression on T reg cells. Results At ten weeks after Tim-3 induction, Tim-3 transgenic mice had larger spleens and lymph nodes. This phenotype was observed to be milder in younger mice. Lymphoid organs in constitutive Tim-3 transgenic mice showed systemic lymphoid hyperplasia. T cells in these mice displayed a more activated phenotype. Overall frequency, numbers and phenotype of Treg cells in the peripheral lymphoid organs were also altered in constitutive Tim-3 transgenic mice. In the inducible Tim-3 mice however, we do not find systemic lymphoid hyperplasia but changes in numbers and phenotype of Treg were consistent with constitutive Tim-3 transgenic mice. Ectopic Tim-3 expression on Treg was also associated with changes in Treg function both in vitro and in vivo. Conclusions TIM-3 is sufficient to change the basic regulatory function of T reg cells, thereby studying how checkpoint therapies effect T reg in tumormicroenvironment and chronic infection may lead us to better Understanding the role of Tim-3 in Treg, and could contribute to novel therapeutic approaches for diseases such as cancer and chronic infection.P398 Activation of the T Cell costimulatory protein CD137 using multivalent bicyclic peptidesKristen Hurov, Punit Upadhyaya, Jessica Kublin, Xueyuan Zhou, Julia Kristensson, Rachid Lani, Gemma Mudd, Katerine van Rietschoten, W. Frank An, Johanna Lahdenranta, Liuhong Chen, Gavin Bennett, Kevin McDonnell, Nicholas Keen, Peter U. Park, PhDBicycle Therapeutics, Lexington, MA, USACorrespondence: Peter U. Park (peter.park@bicycletx.com) Background CD137 (4-1BB/TNFRSF9) is a costimulatory receptor belonging to the TNF receptor superfamily. It was originally cloned as an inducible gene from stimulated helper and cytotoxic T cells and has since been shown to also be expressed on natural killer (NK) cells. Agonistic anti-CD137 antibodies have shown potent, often curative anti-tumour activity in preclinical models. These effects are mainly mediated by cytotoxic T cells and generate long lasting, memory responses. Two human anti-CD137 antibodies, binding to the extracellular domain of CD137, urelumab and utomilumab are currently undergoing clinical testing. Urelumab has shown several single-agent, partial responses, but its use has been hampered by hepatoxicity, whilst utomilumab has shown little or no single agent activity. Methods Bicycles® are a new class of drugs - fully synthetic, constrained bicyclic peptides that combine the attributes of three therapeutic modalities (antibodies, small molecules, and peptides) by delivering high affinity, good PK, and rapid clearance. Their small size (1.5-2 kDa) delivers advantages in tumour penetration, and rapid renal elimination may avoid the liver and GI toxicity often associated with other drug modalities, including certain antibodies. We hypothesised that a fully synthetic Bicycle CD137 agonist with rapid renal clearance, minimal liver interaction and no Fc receptor interaction may induce CD137 mediated anti-tumour activity while avoiding liver toxicity. We screened for CD137 binders with a library of 10e12 Bicycles using phage display and following phage and chemical optimization, a high affinity lead BCY3814 (KD ~30 nM) was selected. Results BCY3814 binds to the human CD137 ligand-binding site. In common with many TNF receptors, CD137 activation requires receptor crosslinking, thus multivalent binders would be expected to recapitulate the action of its natural trimeric ligand. We generated more than 50 different bi-, tri- and tetra-valent variants of BCY3814 with chemical linkers and hinges of various lengths and rigidity using different sites of attachments, while maintaining a compact size (<15 kDa). We developed molecules exhibiting a wide range of potency in a cell-based CD137-dependent reporter assay. In addition, these molecules activate human T cells in vitro as monitored by increased cytokine release. Selected CD137 multimers are being tested in a humanized CD137 mouse model to demonstrate T cell activation and anti-tumour activity, without the liver toxicity reported for urelumab. Conclusions We hypothesise that such molecules could be promising, novel cancer immunotherapy candidates and importantly, they pave the way for development of synthetic agonists of other TNF receptors.P399 Induction of tumor-specific immune responses and modulation of the tumor micro-environment by TLR9 agonist lefitolimod in murine syngeneic tumor modelsKerstin Kapp, PhD1, Barbara Volz1, Detlef Oswald1, Burghardt Wittig, MD, PhD2, Manuel Schmidt, MSc11Mologen AG, Berlin, Germany; 2Advisor to Mologen AG, Berlin, Germany Background Preclinical and ongoing clinical studies support the application of TLR9 agonists for immunotherapy. The immune surveillance reactivator (ISR) lefitolimod is in advanced clinical development for single-agent maintenance treatment in metastatic colorectal cancer (phase III, IMPALA) and extensive disease small cell lung cancer (phase II, IMPULSE). Lefitolimod activates plasmacytoid dendritic cells to secrete interferon-alpha, followed by a broad activation of cells of the innate and adaptive immune system. Lefitolimod therefore provides the necessary and sufficient signals for the initiation of an immunotherapeutic anti-tumor response. Methods It was evaluated, if lefitolimod is able to induce local and systemic anti-tumor immune responses in the murine syngeneic colon carcinoma CT26 and the breast cancer EMT-6 models. The presence and activation state of CD8+ T cells within tumor infiltrating cells was determined via flow cytometry. Tumor antigen-specific T cells were analyzed via IFN-gamma ELISpot using spleen cells stimulated with either tumor cells or the peptide AH1, derived from an immunodominant antigen of CT26 cells. Results Intratumoral administration of lefitolimod resulted in a beneficial modulation of the tumor micro-environment (TME) characterized by increased infiltration of activated CD8+ T cells, which showed an up-regulation of Granzyme B. Notably, an increase of IFN-gamma secreting CD8+ T cells within the spleen was detected after re- stimulation with the tumor-specific AH1 peptide antigen or CT26 tumor cells. This beneficial TME modulation and antigen-specific effects were associated with a markedly reduced tumor growth in the CT26 model. The anti-tumor effect was even more pronounced in the EMT-6 model, where nine out of ten mice showed complete tumor regression. The 9 tumor-free mice subsequently rejected both, the initially used EMT-6 as well as CT26 tumor cells in re-challenge studies, in contrast to age-matched naïve mice. This indicates that treatment with lefitolimod induces a sustained, long-lasting immune memory against shared antigens of both tumor types. Conclusions Treatment of tumors with lefitolimod resulted in a beneficial modulation of the TME with an increase in anti-tumor effector cells. A strong systemic immune response as well as a sustained immune memory against different tumors was induced. These data indicate that lefitolimod provides the essential requirements for use as mono- immunotherapy or as an optimal combination partner of other immunotherapeutic drugs like checkpoint inhibitors in immuno-oncological trials.P400 Tumor-localizing NKp30/ICOSL vIgD fusion proteins direct effective dual CD28/ICOS T cell costimulation to B7-H6+ tumor cells in vitro and tumors in vivoSteven Levin, PhD2*, Lawrence Evans, BS2, Erika Rickel2, Katherine Lewis, PhD2, Daniel Demonte2, Martin Wolfson, BS2, Stacey Dillon, PhD2, Ryan Swanson, BS2, Kristine Swiderek, PhD2, Stanford Peng, MD, PhD21Alpine Immune Sciences, Inc., Seattle, WA, USA; 2Alpine Immune Sciences, Seattle, WA, USACorrespondence: Steven Levin (steve.levin@alpineimmunesciences.com) Background Background: Although checkpoint inhibitor therapies have significantly improved outcomes in multiple cancers, complete and durable responses remain infrequent, possibly attributable to a lack of adequate T cell costimulation and/or activating signals. Novel therapeutic proteins which confer T cell costimulation may be particularly effective anti-tumor therapies, particularly in combination with checkpoint inhibitors. But at the same time, localization of such costimulatory activity to tumors, such as via a tumor-specific targeting antigen, may be simultaneously important to maintain tolerability of such agonist therapeutics. B7-H6, a cell surface immunoglobulin superfamily (IgSF) member which binds the NKp30 receptor, appears to be expressed spe